DINAMIKA HISTORIS BARAT-ISLAM: MISPERSEPSI, PRASANGKA, DAN KONFLIK - Syahirul Alim (Mimbar Agama Budaya, 2020)
Absract. The historical dynamics of the West-Islam always depicted as a phenomenon of misperception, antipathy, and conflicts that have been going on since the 12th century. The events of the Crusades and the spirit of reconquest of areas once occupied by Islam, leaving a bad-trail imprint in almost all perspectives of Western society towards Islam. Western antipathy was shown through negative sentiments, such as the term "saracen" to Muslim troops and the title of "Moor" which is still used by Western elites when they invaded and control various Muslim-majority areas. The heritage of Islamic civilization for the progress of the Western World is only valued to the extent of the "threat" about the revival of the glory of Islamic civilization that had ruled the world for about 7 centuries. The efforts of some Western scholars who are more objective perceived in understanding Islam, apparently are not so influential and Islam was still misunderstood by the West, even Islamophobia was becoming a phenomenon that strengthens as a form of Western fear of Islam. This paper seeks to portray the historical dynamics of West-Islam from various perspectives descriptively-analysis through a historical approach. Historical awareness is needed, so that too excessive and baseless assessments of anything should be avoided, because history was a series of past events that can provide information in the present, functioning as a frame of knowledge in placing a reality in a fitting and objective manner. Abstrak. Dinamika historis Barat-Islam selalu menggambarkan fenomena mispersepsi, antipati, bahkan konflik yang telah berjalan sejak abad ke-12. Peristiwa Perang Salib dan semangat penaklukan kembali wilayah-wilayah yang pernah dikuasai Islam oleh pasukan Salib, meninggalkan jejak buruk dalam hampir seluruh perspektif masyarakat Barat terhadap Islam. Antipati Barat ditunjukkan melalui sentimen negatif, seperti sebutan “saracen” kepada pasukan Muslim dan gelar orang “Moor” yang tetap dipakai kalangan elit Barat ketika mereka melakukan invasi dan penguasaan atas berbagai wilayah berpenduduk mayoritas Muslim. Warisan peradaban Islam bagi kemajuan Dunia Barat hanya dihargai sebatas “ancaman” tentang kebangkitan kembali kejayaan peradaban Islam yang pernah menguasai dunia selama kurang lebih 7 abad. Upaya beberapa sarjana Barat yang lebih objektif dalam memahami Islam, ternyata tidak begitu berpengaruh dan Islam tetap disalahpahami oleh Barat, bahkan Islamofobia menjadi fenomena yang menguat sebagai bentuk ketakutan Barat terhadap Islam. Tulisan ini berupaya memotret dinamika historis Barat-Islam dari berbagai perspektif secara deskriptif-analisis melalui pendekatan historis. Kesadaran historis diperlukan, sehingga penilaian yang terlampau berlebihan dan tanpa dasar terhadap hal apapun seharusnya dapat dihindari, sebab sejarah merupakan rangkaian peristiwa masa lalu yang dapat memberikan informasi pada masa kini, berfungs sebagai bingkai pengetahuan dalam menempatkan sebuah realitas secara pas dan objektif.